GEOLOGI DAN POTENSI BAHAN GALIAN BIJIH BESI DAERAH ACEH BARAT DAYA - -, Iyan Haryanto (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
The geology of the Aceh Baratdaya has been controlled by convergence of the Eurasian and Indian lithospheric plates since the Mesozoic era. Various types of rock—including the metamorphic, meta-sedimentary, volcanic, and plutonic rocks—and the associated economic mineral deposits have been formed by diverse geologic proceses (i.e., sedimentation, lithification, metamorphosis, crystallization, and structural processes) associated with convergent plate interactions.The magnetic iron ores in the study area are interpreted as the crystallization product of hydrothermal solutions. Genetically, the iron ore in the study area is of lateritic type. Most of the ores in the study area are spread in northwest-southeast direction, in harmony with the general trend of faults and folds.